Dekonstruksie van dogma: "n Eietydse ondersoek na die spore van die leer van die twee nature van Jesus - Aarde, Andries van (Hervormde teologiese studies, 1999)
Deconstructing dogma: Tracking the pathways of the creed concerning Jesus' two natures from a present-day perspective. The article presumes that religious language develops according to four phases: a movement from foundational religious expeience to metaphoical language usage to confessional formulae to dogma. It is argued that Jesus' call upon God as father should be seen as a foundational religious expeience which was expressed by means of a familial metaphor. Writers Of New Testament books refer also to the followers of Jesus as children of God. Paul and Mark point explicitly to the dual nature of a child of God: being born as human and being born spiritually from God. The confessional formulae in the Nicene Creed about the two natures of Jesus as ontolagical entities intended to emphasize Jesus' humanness. The dogma, which originated during the sixteenth and seventeenth centuries, continued to convey this tendency. Thearticle concludes that, for Chistians today, the metaphor "child of God" is still functionul to express a foundational religious experience.